Academic Leadership : Fundamental Building Blocks. - Vilkinas, Tricia; Leask, Betty; Ladyshewsky, Richard (Australian Learning and Teaching Council (ALTC), 2009)
Final report from a study that focused on the front-line managers, namely the academic coordinators, of two Australian universities. It assessed the leadership capability of these staff using the Integrated Competing Values Framework (ICVF) as its theoretical foundation. It also investigated how effective academic coordinators were and what factors impacted on their performance and made their role more attractive. Professional development workshops were designed to further develop the leadership capability of these front-line managers. In addition, resources were also produced to support the workshops. A professional development framework was designed and tested, and a website was developed to support the project. The report concludes that the front-line managers in this study were capable of providing the academic leadership needed, even though they had no formal authority. These managers need on-going support by senior managers and regular development opportunities if they are to continue to provide the kind of leadership that results in high quality teaching and learning outcomes. While these results are based on the outcomes from two universities, a subsequent study has commenced that will take the work from the present study across the sector.